2014
DOI: 10.1519/jsc.0000000000000351
|View full text |Cite
|
Sign up to set email alerts
|

Does an In-Season Detraining Period Affect the Shoulder Rotator Cuff Strength and Balance of Young Swimmers?

Abstract: A cross-sectional study on physical and sedentary activity and health-related quality of life in institutionalized vs. non-institutionalized elderly Differences between institutionalized and non-institutionalized elderly were found in moderate-intensity activities and walking, a favour of non-institutionalized. The institutionalized elderly remain more minutes in sedentary activity. Also, were observed differences between both groups in physical component of HRQoL, a favour of non-institutionalized elderly. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
1
14
0
1
Order By: Relevance
“…Similar interventions have been conducted in swimming, and while Batalha et al demonstrated a significant increase in ER peak torque and ER/IR ratio after a 16‐week intervention, Hibberd et al found no significant effects after 6 weeks 28 . The latter study used eleven strength exercises for different muscle groups and two IR stretching exercises 28,29 …”
Section: Discussionmentioning
confidence: 92%
“…Similar interventions have been conducted in swimming, and while Batalha et al demonstrated a significant increase in ER peak torque and ER/IR ratio after a 16‐week intervention, Hibberd et al found no significant effects after 6 weeks 28 . The latter study used eleven strength exercises for different muscle groups and two IR stretching exercises 28,29 …”
Section: Discussionmentioning
confidence: 92%
“…Although propulsive force depends not only on the produced strength, but also on the limbs´ orientation (Leong, 2015) and even on how much the fingers are spread (Marinho et al, 2010), it is known that an overload is caused in the shoulder joint. As such, a shoulder rotators imbalance is created, as reported in competitive swimming (Batalha et al, 2014) and might eventually be related to shoulder injury (Byram et al, 2010) and scapular dyskinesis (Madsen et al, 2011). Swimming requires a large range of motion of the shoulders, with emphasis on circumduction movements that have varying degrees of internal and external rotation and scapular protraction and retraction (Tovin, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Shoulder muscle imbalances indicated by low values of the ER/IR ratio, have been observed in individuals with glenohumeral joint instability, and are considered a shoulder injury risk factor (Lin, 2015;Niederbracht et al, 2008). It has previously been shown that in swimming, an in-water training macrocycle is enough to trigger muscle imbalances in swimmer´s shoulder rotators (Batalha et al, 2014). This is due to a significant increase in IR strength, with no concurrent increase in ER strength (Batalha et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations